Prevalence of canaliculitis after smartplug insertion during long-term follow-up. Issue 8 (26th February 2015) - Klein-Theyer, Angelika; Boldin, Ingrid; Rabensteiner, Dieter Franz; Aminfar, Haleh; Horwath-Winter, Jutta
Abstract : Purpose: To evaluate the long-term prevalence of canaliculitis associated with the use of SmartPlugs. Methods: This retrospective study included 42 eyes of 25 dry eye patients at our institution who received a SmartPlug insertion between 2004 and 2008. Irrigation of the lacrimal system was performed in all patients prior to SmartPlug insertion to ensure the patency of the system. The median follow-up time was 7.9 (5.6–10.5) years after plug insertion. Results: Six patients (seven eyes) of 25 patients (42 eyes) developed canaliculitis. The prevalence of canaliculitis per patient was 24%, and the prevalence of canaliculitis per SmartPlug was 16.6%. The median time from SmartPlug insertion to the onset of canaliculitis was 4.7 (1.4–6.0) years. The median age of the affected patients was 61.5 (36–74) years. Five of these patients were women and one was man. The pathogens were identified as Actinomyces in four eyes and as Staphylococcus aureus in three eyes. In five patients (six eyes), the canaliculitis was resolved by the application of topical antibiotics and repeated lacrimal irrigations with antibiotics and povidone-iodine. In one patient, a canaliculotomy was necessary to cure the condition. Conclusions: The late onset of complications after SmartPlug insertion requires long-term observation to identify the majority of complications associated with SmartPlugs. In our patients with a follow-up of up to 10.5 years, the use of SmartPlugs was associated with the highest prevalence of canaliculitis published thus far.